Clinical development and marketing application review times for novel orphan-designated drugs - Demirci, Ebru; Knicley, Jennifer; Fiorentino, Lori (Frontiers in Medicine, 2024)
Development of an orphan-designated drug has been more challenging and financially less attractive than that of other drugs due to low prevalence of the condition, poorly defined biomarkers and lack of experience of healthcare providers in diagnosing and treating the condition. Guidance and incentives in some countries support the sponsors in developing orphan-designated drugs despite the challenges. Expedited regulatory programs as offered by the United States (US) Food and Drug Administration (FDA) and the European Medicines Agency (EMA) support the development of drugs, provide shorter marketing application review times or provide preliminary approval. In this study, we analyze marketing application review times in the US and in the European Union (EU) and clinical development times for novel, i.e., containing new molecular entity, orphan-designated drugs that were approved in the US between 1 June 2020 and 31 May 2023, and their correlation with expedited regulatory programs. Seventy-three marketing applications for novel orphan-designated drugs were approved by the FDA, and 39 also received a positive opinion from the EMA. The marketing application review time by the FDA for the 73 novel orphan-designated drugs approved in the US was 244 days (n=73, median), and the marketing application review time by the EMA for the 39 drugs that were also approved in the EU was 353 days (n=39, median). The typical clinical development time for a novel orphan-designated drug was 7.2 years (n=72).